2006
DOI: 10.1093/mollus/eyl001
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Hox genes in molluscs: a comparison among seven morphologically diverse classes

Abstract: Hox genes have pivotal roles in animal body plan formation. We identified Hox genes and inferred the organizations of the Hox gene hypothetical ancestral cluster by a polymerase chain reaction (PCR) survey for the phylum Mollusca, so as to assess possible correlations with morphological diversity. All the extant classes, except for Monoplacophora, were examined, namely Solenogastres, Caudofoveata, Polyplacophora, Cephalopoda, Gastropoda, Scaphopoda, and Bivalvia. The result showed that the molluscs primarily p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…As regards the central class, the Nmi-Scr sequence reveals high similarity with the Scr of other molluscs, with conservation of the characteristic tyrosine and lysine amino acid residues in positions 20 and 22, respectively, and a serine in position 35, as was found in the Hox5a sequences of the chiton and the solenogast studied by Iijima et al (2006). At variance with Iijima et al (2006), we identified a single sequence attributable to the Scr gene in N. mirandus.…”
Section: Resultssupporting
confidence: 51%
See 4 more Smart Citations
“…As regards the central class, the Nmi-Scr sequence reveals high similarity with the Scr of other molluscs, with conservation of the characteristic tyrosine and lysine amino acid residues in positions 20 and 22, respectively, and a serine in position 35, as was found in the Hox5a sequences of the chiton and the solenogast studied by Iijima et al (2006). At variance with Iijima et al (2006), we identified a single sequence attributable to the Scr gene in N. mirandus.…”
Section: Resultssupporting
confidence: 51%
“…The orthology of Nmi-lab to paralog group 1 is supported by diagnostic amino acid residues in positions 27, 39 and 41. The Nmi-lab sequence is identical to the amino acid sequence of the Hox1 of the chiton Acantopleura japonica (Iijima et al, 2006) and is highly similar to the sequences of pectinids P. maximus (Canapa et al, 2005) and Pecten yessoensis (Iijima et al, 2006) due to the serine in position 35. The Nmi-pb sequence is identical to that of the pb of other protostomes, with the amino acid aspartic acid in position 37, which is present in all the organisms analysed so far with the exception of the scaphopod Dentalium octangulatum (Iijima et al, 2006).…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations